A fluoride activated methylene blue releasing platform for imaging and antimicrobial photodynamic therapy of human dental plaque. Issue 93 (6th November 2018) - Wei, Peng; Xue, Fengfeng; Shi, Yunming; Strand, Ross; Chen, Hui; Yi, Tao
Abstract : A fluoride activated methylene blue releasing platform was developed for imaging and antimicrobial photodynamic therapy of human dental plaque. Abstract : We report a F − activated methylene blue (MB) releasing platform for imaging and antimicrobial photodynamic therapy (aPDT). By utilizing this platform, one of the selected probes, FD-F3, displays a remarkable near-infrared fluorescence and absorption increase towards F − with good selectivity and low detection limit. This probe has been successfully applied for visualizing F − and performing F − activated aPDT in naturally grown human plaque biofilms.